Analisis Kalimat Efektif Pada Teks Opini Dalam Laman “Harian Jogja” Edisi Agustus 2023 Sebagai Bacaan Edukasi - Audya Nilam Nariswari; Dewi Trisnawati; Elsa Revalina; Hawa Amwalya Akasyah; Nurlaili Ismiati; Asep Purwo Yudi Utomo; Ahmad Fajar Habibi (Universitas Palan, 2024)
Syntax is a branch of linguistics that studies phrases, clauses and sentences. This article focuses more on analyzing sentences in a text, where the sentence itself is a language unit that is relatively independent, has final intonation, and actually or potentially consists of clauses. The purpose of this study is to determine the effectiveness of sentences in opinion texts on the August 2023 edition of “Harian Jogja” as educational reading in terms of sentence structure and word choice. The type of research method used is descriptive qualitative research method and syntactic approach. The research data are the results of identifying ineffective sentences used in opinion texts on the “Harian Jogja” August 2023 Edition as Educational Reading. The data collection technique used is the syntactic approach in the form of listening and note-taking techniques. The informal method is used as a data presentation technique in this research. The data presentation is written in the form of a table containing some ineffective sentences and their improvements. From the analysis, 121 sentences were found consisting of 58 effective sentences and 63 ineffective sentences. In the opinion text titled “Peubahan Iklim dan Peran Masyarakat Memilah Sampah” there are 17 effective sentences and 22 ineffective sentences. In the opinion text titled “Mencermati Arsitektur RAPBN 2024,” there are 19 effective sentences and 18 ineffective sentences. In the opinion text titled “Peluang dan Tantangan Pertukaran Karbon,” there are 22 effective sentences and 23 ineffective sentences. This research produces several ineffective sentences which are classified into 3 namely waste in the use of words, inaccuracy in the use of words, and the last is the incompatibility of the information provided. In this analysis, the researcher uses one of the opinion texts as an example or sample, namely the opinion text entitled “Perubahan Iklim dan Peran Masyarakat dalam Memilah Sampah”. From the analysis of the opinion text which is composed of 39 sentences, there are 22 ineffective sentences. This study is useful as a guideline for writing effective sentences, besides that writers can pay more attention to writing in an opinion text that is by the rules of language.